2015
DOI: 10.1007/s13222-015-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward GPU-accelerated Database Optimization

Abstract: For over three decades, research investigates optimization options in DBMSs. Nowadays, the hardware used in DBMSs become more and more heterogeneous, because processors are bound by a fixed energy budget leading to increased parallelism. Existing optimization approaches in DBMSs do not exploit parallelism for a single optimization task and, hence, can only benefit from the parallelism offered by current hardware by batch-processing multiple optimization tasks.Since a large optimization space often allows us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Leis et al [28,30] evaluate the influence of several plan enumeration algorithms and the impact of considering bushy trees. Several recent approaches have been proposed to optimize the plan enumeration phase by using GPUs [37,38] and deep reinforcement learning models [34,35]. In this work, we propose an adaptive graph traversal algorithm that efficiently explores the search space.…”
Section: Related Workmentioning
confidence: 99%
“…Leis et al [28,30] evaluate the influence of several plan enumeration algorithms and the impact of considering bushy trees. Several recent approaches have been proposed to optimize the plan enumeration phase by using GPUs [37,38] and deep reinforcement learning models [34,35]. In this work, we propose an adaptive graph traversal algorithm that efficiently explores the search space.…”
Section: Related Workmentioning
confidence: 99%
“…Academics and industry are beginning to explore some new ways to accelerate the performance of data processing through software/hardware co-design. Instructionlevel optimization [16], coprocessor query optimization [17,18], hardware customization [19], workload hardware migration [20], increasing hardware-level parallelism [21], hardware-level operators [22], and so on are used to provide hardware-level performance optimization. However, the differences between the new processor and x86 processor fundamentally change the assumptions of traditional database software design on hardware.…”
Section: System Architecture and Design Schemes In Platforms With Newmentioning
confidence: 99%
“…Nowadays, the processor technology moves from multi-core to many-core which greatly differs from the multi-core processor in terms of core integration, number of threads, cache structure, and memory access. The object that should be optimized has been turned into SIMD [84,85], GPUs, APUs, Xeon Phi coprocessors, and FPGAs [18,[86][87][88]. The query optimization is becoming more and more dependent on the underlying hardware.…”
Section: Query Processing and Optimization In Platforms With New Hardmentioning
confidence: 99%
“…A good overview about this topic can be found in a recent survey by Özcan et al [45]. A key enabling factor for HTAP systems is modern hardware: modern hardware promises novel ways for data process-Marcus Pinnecke pinnecke@ovgu.de 1 Institute of Technical and Business Information Systems, Database and Software Engineering Group, University of Magdeburg, Magdeburg, Germany ing of relational [14,25] and non-relational data [42,49], as well as benefits for several database system components, such as query optimization [26,41]. Appuswamy et al even suggested to use the term H 2 TAP whenever hybridization of workloads is combined with heterogeneity of hardware [6], effectively emphasizing the role of modern hardware.…”
Section: Introductionmentioning
confidence: 99%